THE DEVELOPMENT OF THEATER IN THE CHECHENO-INGUSH ASSR IN THE 40―60S’ OF THE XX CENTURY - El'buzdukaeva, Tamara Umarovna (History, Archeology and Ethnography of the Caucasus, 2019)
The selection of the topic for publication is brought into focus by the decree of the President of the Russian Federation on the announcement of 2019 as the Year of Theater, as well as preparation for the celebration of the 75th anniversary of the Victory over Nazi Germany. The relevance of the choice of theatrical culture of the Chechen Republic in the object of study is also related to its lack of information on this topic. The study analyzes the activities of republican theaters in military conditions; reconstruction of the basic principles and methods of functioning of the Chechen-Ingush theaters in the years of the restoration of autonomy and the “ottepel” (thaw) of the 1960s’.In the years of the Great Patriotic War, the Chechen-Ingush Theater was rebuilt in a military manner and confided to barracks. The propaganda teams that spoke in all corners of the republic, in hospitals and military units, in field camps and at enterprises raised the fighting spirit of the soldiers. Many artists of the republic went to the front and fought against the enemy in arms.The development of the Chechen-Ingush culture in the second half of the 1950s’ – 1960s’ of the XX century occurred in the conditions of democratization of life of the Soviet society, the restoration of the republic’s autonomy, the atmosphere of freedom of creativity. In the mid-1960s’, with the arrival of students of the academic M. Soltsayev and R. Khakishev’s Leningrad school, the repertoire of the Chechen-Ingush theater is replenished with works of heroic romance and high poetry. The performances of Russian, Georgian, Azerbaijani, Ossetian, Balkarian, Dagestan and other authors appear. In the 60s’ of the XX century, Chechen-Ingush Theater was among the ten best national theaters of the Soviet Union.The methodological basis of the research is the dialectical approach, which allowed studying the theatrical art of the Chechen-Ingush ASSR on the principles of historicism, objectivity and comprehensive study of the subject. The logical method made it possible to analyze the sources, to establish the degree of knowledge of the problem in the national historiography, to determine the purpose and objectives. With the help of the historical-genetic method, the theatrical life of the republic during the war, the restoration of autonomy and the “ottepel” of the 1960s’ is revealed.
Keywords: front-line brigades; repertoire policy; national theater; Checheno-Ingush ASSR; national dramaturgy; new aesthetics period.